Integrative Assessment of Chemical-Sensory Interactions in Poultry Meat: Predictive Insights from Frozen Storage Dynamics at −18°C - Khalaf, Ali Ahmed; Al-Badri, Zina Rashid Khirija; Kareem Al-Zubaidi, Zainab Hussein (American Journal of Biology and Natural Sciences, 2025)
Background: Frozen storage at −18°C is a widely adopted method for extending poultry meat shelf life; however, prolonged storage can alter its chemical composition and sensory attributes. Understanding the correlation between these chemical changes and sensory quality is crucial for optimizing storage practices. Objective: This study aimed to determine the relationships between variations in the chemical composition of poultry meat (moisture, protein, fat, and ash) during frozen storage and corresponding changes in sensory traits (color, flavor, tenderness, and juiciness). Methods: Fresh broiler breast samples were stored at −18°C for 0, 1, 2, 3, and 6 months. Proximate composition was analyzed following AOAC (2005) methods, and sensory evaluation was performed by a trained panel using a 9-point hedonic scale. Pearson correlation coefficients were calculated to assess the associations between chemical and sensory parameters. Results: Moisture content showed moderate to strong positive correlations with flavor (r = 0.59), tenderness (r = 0.62), and juiciness (r = 0.48), indicating that water retention plays a key role in maintaining sensory quality. Protein content exhibited weak to moderate negative correlations (−0.39 to −0.49) with sensory traits, reflecting structural changes in muscle fibers over time. Fat content had weak negative associations (−0.24 to −0.40), while ash content showed strong negative correlations with all sensory attributes (−0.74 to −0.75), suggesting mineral concentration as an indicator of advanced quality deterioration. Conclusion: The findings highlight moisture loss and ash increase as primary chemical drivers of sensory decline in frozen poultry meat, with secondary effects from protein and fat changes. Implementing strategies such as vacuum packaging, antioxidant supplementation, or magnetized water treatment may help mitigate these quality losses.